Glow-Wire Analysis of Polypropylene Blends for Mechanical and Marine Engineering Applications - Firdaus, Himma; Supono, Ihsan; Pratama, Anandito Adam; Istanto, Iwan; Prabowo, Aditya Rio; Kusnandar, Nanang; Kasiyanto, Iput; Wijaya, Rahman; Lailiyah, Qudsiyyatul; Budiana, Eko Prasetya; Yaningsih, Indri; Akbar, Hammar Ilham; Imanullah, Fahmi (Civil Engineering Journal, 2025)
Polymer materials are widely used due to their versatility; however, their vulnerability to fire is a significant concern, especially under electrical influences on engineered mechanical designs and marine structure applications. This study examines the fire resistance of a polypropylene (PP) blend using Glow-Wire Flammability Index (GWFI) and Glow-Wire Ignition Temperature (GWIT) tests. While previous research typically relies on flame-retardants to address flammability, this work proposes using a simple 1:1 weight ratio blend of two distinct PP types. This specific PP blend was selected to provide balanced material properties and improved processing consistency. The results from glow-wire tests were compared with previous findings to evaluate flammability performance. Our findings reveal that although the PP blend offers enhanced fire resistance compared to neat PP, it remains inferior to PP-containing flame-retardant additives. The outcomes suggest that this blended PP may be suitable for applications where mechanical properties, cost-effectiveness, and recyclability precede fire resistance, such as engineered automotive interiors, mechanical design of marine transportation, and low-risk electrical components in engineering infrastructure. This initial research contributes valuable insights into the fire behavior of PP blends. Moreover, it establishes a foundation for future investigations into polymer fire resistance, encouraging additional glow-wire testing on other polymer systems.